(untitled) (Research, Society and Development, 2023)
Introduction: Postpartum depression (PPD) is a prevalent condition among women, which occurs due to significant physical, hormonal, and emotional changes that occur during this period. Its development can be associated with various risk factors that can be identified even during the perinatal period. Objective: The study aims to identify risk factors related to the occurrence of PPD with the intention of preventing them and avoiding worse outcomes. Methods: This is a narrative literature review conducted through the collection and analysis of data on the topic "risk factors associated with postpartum depression." The descriptors used were "postpartum depression," "risk factors," "pregnancy," and "postpartum period." Results: It was possible to group the identified risk factors into four categories: obstetric, psychological, socioeconomic, and behavioral. Conclusion: These factors have proven to be of great relevance to the development of PPD, impacting family relationships and the health of both the mother and the baby.